EFEKTIVITAS MODEL PEMBELAJARAN DISCOVERY LEARNING DALAM MENINGKATKAN HASIL BELAJAR PADA SUBTEMA SUHU DAN KALOR SISWA KELAS V SD ISLAM PESANGGRAHAN SEMARANG - Nadia Amalia Dara Puspitasari Nadia; Qoriati Mushafanah (STKIP Subang, 2023)
The background that prompted this research was to show that the learning level of students was still relatively low, so that there were still many students who scored below the KKM, student activities when learning was not active and the independence of students was still lacking.The problem of this research is